Protective effect of α-asarone against nicotine-induced seizures in mice, but not by its interaction with nicotinic acetylcholine receptors - Chellian, Ranjithkumar; Pandy, Vijayapandi (Elsevier, 2018)
Alpha-asarone is one of the bioactive phytochemicals present in the rhizomes of Acorus species and demonstrated its anticonvulsant activity in rodents. Alpha-asarone protected mice from the gamma-aminobutyric acid (GABA) type A receptor antagonist or N-methyl-D-aspartate (NMDA) receptor agonist-induced seizures. In our recent study, α-asarone attenuated the nicotine withdrawal-induced depression-like behavior in mice. The seizures induced by nicotine is mediated through the activation of nicotinic acetylcholine receptors (nAChRs) and stimulation of NMDA receptors. Therefore, we hypothesized that α-asarone might be effective against nicotine-induced seizures. Also, the interaction of α-asarone with nAChRs is unknown. In this study, we investigated the effect of α-asarone on the locomotor activity and body temperature in mice. In addition, we studied the effect of α-asarone on nicotine-induced seizures in mice. Finally, we assessed in vivo pharmacodynamic interaction of α-asarone with nAChRs using nicotine-induced hypomotility and hypothermia tests in mice. The results of this study showed that the α-asarone (50–200 mg/kg, i.p.) and diazepam (5 mg/kg, i.p.) treatment significantly decreased the locomotor activity and body temperature in mice. Furthermore, α-asarone (50–200 mg/kg, i.p.) and diazepam (5 mg/kg, i.p.) pretreatment significantly prolonged the onset time of nicotine-induced seizures in mice. However, α-asarone (30 and 50 mg/kg, i.p.) pretreatment did not inhibit the nicotine-induced hypomotility or hypothermia in mice. Conversely, mecamylamine (1 mg/kg, s.c.) pretreatment completely blocked the nicotine-induced seizures and significantly prevents the nicotine-induced hypomotility and hypothermia in mice. Overall, these results suggest that the protective effect of α-asarone against nicotine-induced seizures did not mediate through the antagonism of nAChRs. We also postulated that the GABAergic and glutamatergic activities of α-asarone could be involved in its protective effect against nicotine-induced seizures and based on this aspect further studies are required.